Integrating woodland caribou needs and forestry: perspectives of Alberta's forest industry - Brown, W. Kent (Rangifer, 1998)
Much of Alberta's woodland caribou (Rangifer tarandus caribou) range outside protected areas is subject to commercial forest management. In this paper, I discuss some perspectives of the forest industry regarding caribou-related issues. Six forest companies holding Forest Management Agreements (FMAs) in Alberta were polled. Forest managers were most concerned about 2 aspects of caribou management: reductions of annual allowable cut (AAC) that may be necessary to provide for caribou habitat needs; and management of public access. Perceived information gaps fell into 3 categories: caribou demographics (population size, trends and densities); primary limiting factors of caribou populations (including the influence of human activity); and caribou habitat requirements (including the effects of timber harvest on caribou habitat). Increased costs associated with consideration of caribou have been incurred at the planning and operational levels. However, those costs have been low, primarily because much proposed harvest in caribou ranges has been deferred. Costs are expected to increase substantially in the future as timber from caribou ranges is required to meet harvest objectives. Other issues identified included: the desire for an adaptive management approach to caribou-forestry interactions; the need to incorporate natural-disturbance-regime models into forest planning; consideration of the cumulative effects on caribou of all industrial and recreational activities; and unmanaged harvest by First Nations people. A list of caribou-related projects conducted or supported by forest companies in Alberta during the past 5 years is provided.